2020
DOI: 10.1177/0036933020956316
|View full text |Cite
|
Sign up to set email alerts
|

Management of appendicitis during COVID-19 pandemic; short-term outcomes

Abstract: Background and aim COVID-19 pandemic has predisposed patients undergoing surgery to post-operative infection and resultant complications. Appendicitis is frequently managed by appendicectomy. After the onset of the pandemic, selected cases of appendicitis were managed with antibiotics which is a recognised treatment option. Our objective was to compare the management of appendicitis and post-operative outcomes between pre- and post-COVID-19. Methods Ninety-six patients were identified from before the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 19 publications
8
48
0
2
Order By: Relevance
“…Another study by Patel et al 16 found no significant difference in complication rates of NOM in the setting of COVID-19 (1/24) and before COVID-19 (1/6) (p = 0.36). The adoption of NOM as a main treatment strategy during the pandemic did not increase readmission rates significantly as reported by Ganesh et al 13 (9.4% vs 12.5%, p = 0.75) nor increased the length of hospital stay. 13,16 Outcome of NOM in COVID-19 Positive Patients Two studies 15,22 reported on the outcomes of NOM in patients with COVID-19.…”
Section: Comparing Outcomes Of Nom Of Acute Appendicitis Before and Asupporting
confidence: 63%
See 3 more Smart Citations
“…Another study by Patel et al 16 found no significant difference in complication rates of NOM in the setting of COVID-19 (1/24) and before COVID-19 (1/6) (p = 0.36). The adoption of NOM as a main treatment strategy during the pandemic did not increase readmission rates significantly as reported by Ganesh et al 13 (9.4% vs 12.5%, p = 0.75) nor increased the length of hospital stay. 13,16 Outcome of NOM in COVID-19 Positive Patients Two studies 15,22 reported on the outcomes of NOM in patients with COVID-19.…”
Section: Comparing Outcomes Of Nom Of Acute Appendicitis Before and Asupporting
confidence: 63%
“…The adoption of NOM as a main treatment strategy during the pandemic did not increase readmission rates significantly as reported by Ganesh et al 13 (9.4% vs 12.5%, p = 0.75) nor increased the length of hospital stay. 13,16 Outcome of NOM in COVID-19 Positive Patients Two studies 15,22 reported on the outcomes of NOM in patients with COVID-19. Overall, seven patients with COVID-19 were treated initially with NOM, with a failure rate of 43% at discharge.…”
Section: Comparing Outcomes Of Nom Of Acute Appendicitis Before and Asupporting
confidence: 63%
See 2 more Smart Citations
“…Second, in areas of diminished operative capacities due to high numbers of COVID-19 patients a conservative approach to appendicitis in situations of overwhelming strain on the health system has been advocated (30)(31)(32). Nevertheless, data from NYC metropolitan region showed that even in regions with crushing hospital burden it was still possible to commit to surgical care of pediatric patients during the COVID-19 surge (8).…”
Section: Discussionmentioning
confidence: 99%